2009
DOI: 10.1097/hjh.0b013e32831fda3a
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphisms of the angiotensin II type 1 receptor gene and diastolic heart failure

Abstract: We identified risk-conferring genetic variants of the AGTR1 gene for DHF in a Chinese population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(48 citation statements)
references
References 28 publications
1
46
0
1
Order By: Relevance
“…[25][26][27] Our recent studies found that patients with the ACE I/D gene D allele and AT1R gene A1166C C allele in RAS genes were more likely to develop DHF. 28,29 In this study, we demonstrated that the ACE I/D gene D allele and AT1R gene A1166C C allele were associated not only with the development of DHF but also with the long-term prognosis. Furthermore, the genetic association of the ACE I/D polymorphism with mortality was prominent in those who did not take ACE inhibitors, but was not significant in the patients who took ACE inhibitors.…”
Section: Survival Free Of Death From Cardiovascular Eventsmentioning
confidence: 52%
“…[25][26][27] Our recent studies found that patients with the ACE I/D gene D allele and AT1R gene A1166C C allele in RAS genes were more likely to develop DHF. 28,29 In this study, we demonstrated that the ACE I/D gene D allele and AT1R gene A1166C C allele were associated not only with the development of DHF but also with the long-term prognosis. Furthermore, the genetic association of the ACE I/D polymorphism with mortality was prominent in those who did not take ACE inhibitors, but was not significant in the patients who took ACE inhibitors.…”
Section: Survival Free Of Death From Cardiovascular Eventsmentioning
confidence: 52%
“…However, the other three candidate genes, namely, AGTR1, PRRC2A, and CALCA, were not found to be associated with hypertension in the Chinese Han population after adjustment by age and gender; these findings disagree with those of previous studies. Angiotensin II receptor type-1 (AGTR1) is a G-protein coupled receptor for angiotensin II, especially in the heart and kidney, and has been studied in many health conditions, including heart failure and stroke (Henskens et al, 2007;Wu et al, 2009). AGTR1 polymorphisms are associated with the susceptibility to hypertension and prehypertension in the American population (Mottl et al, 2008;Fung et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that AGTR1 polymorphisms are related to susceptibility to EH. [7][8][9]22 AGTR1 played an important role in vasoconstriction, aldosterone and vasopressin release and salt and water retention. RAAS was implicated as one major effector of EH.…”
Section: Discussionmentioning
confidence: 99%